Long-term drying trend during 51.8–37.5 Ma in the Nangqian Basin, central-eastern Qinghai–Tibet Plateau - Li, Shangkun; Ma, Xueyun; Jiang, Shaohua; Wang, Gen; Zhang, Ting; He, Wei; Yu, Xiaoli; Ma, He; Zhang, Pengyuan; Wei, Jingyi; Wang, Yongli; Wei, Zhifu (Frontiers in Earth Science, 2022)
Since the Cenozoic, the earth entered a period of relatively active tectonic movement, which led to significant environmental and climatic shifts, including inland drought in Asia, global cooling, and the formation of the Asian monsoon. The Asian aridification has a far-reaching impact on the human living environment, and so do the climate changes in China. The beginning, strengthening, and ending times of the inland drought in Asia have been a long-concerned issue. Therefore, it is necessary to reveal the starting time, evolution process, and underlying driving mechanisms. Because of its unique topography and geographical location, the Qinghai–Tibet Plateau is known as the “starter” and “amplifier” of global climate change. It is a key area and an ideal “laboratory” for long-time scale climate change. Located in the central-eastern part of the Qinghai–Tibet Plateau, the Nangqian Basin is not only the confluence area of major monsoons and westerly winds but also the boundary between humid and arid areas. Moreover, the Nangqian section in the basin has a long continuous sedimentary sequence, making it a good carrier for long-time scale climate change research. In this study, biomarkers and total organic carbon (TOC) in the sedimentary strata of the Nangqian Basin in the central-eastern Qinghai–Tibet Plateau were used to reconstruct the paleoclimate and paleovegetation evolution history over the time interval of 51.8–37.5 Ma. According to the climatic index of the Nangqian Basin, the climate evolution history can be divided into three stages. StageⅠ: during 51.8–46.4 Ma, the depositional environments at this stage were mainly a braided river and an ephemeral shallow pond/lake environment. Also, the value of CPI, δ13Cn-alkanes, and total organic carbon (TOC) was low; meanwhile, ACL value increased with nC27/nC31 decrease, and these obvious change trends might be affected by the mixing of terrestrial sediments brought by rivers. The main peak carbons were nC22 and nC23, the vegetation type was predominantly woody plants, and the climate was relatively humid. Stage Ⅱ: during 46.4–42.7 Ma, Paq and nC27/nC31 values decreased gradually, and ACL, δ13Cn-alkanes, and CPI values increased slowly. Also, the main peak carbon number changed from low to high, and the vegetation type varied from woody to herbaceous. All these proxies displayed that the climate became more arid. Stage Ⅲ: during 42.7–37.5 Ma, Paq, ACL, and nC27/nC31 values did not vary too much, δ13Cn-alkanes values increased slightly, and ACL values decreased slightly, while the main peak carbon number, TOC, and CPI increased significantly, indicating that the climatic conditions continued to get dryer, which may have been affected by the MECO events. In addition, through the comparative study of the climate evolution history of the Eocene in the Nangqian Basin reconstructed by the multi-index system, together with the climate change in the adjacent area, the retreat process of the Paratethys Sea, the global deep-sea oxygen isotopes, and the global atmospheric CO2 concentration, it is considered that the Eocene climate change in the Nangqian Basin is mainly affected by the global climate change and the retreat of the Paratethys Sea. The uplift of the Qinghai–Tibet Plateau and the increase of altitude have little influence on the water vapor of the Nangqian Basin, and the basin was rarely affected by the South Asian monsoon.